2016
DOI: 10.1001/jamasurg.2016.1689
|View full text |Cite
|
Sign up to set email alerts
|

Association of Loss of Independence With Readmission and Death After Discharge in Older Patients After Surgical Procedures

Abstract: Loss of independence, a patient-centered outcome, was associated with postoperative readmissions and death after discharge. Loss of independence can feasibly be collected across multiple hospitals in a national registry. Clinical initiatives to minimize LOI will be important for improving surgical care for older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
102
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 147 publications
(106 citation statements)
references
References 23 publications
4
102
0
Order By: Relevance
“…In Surgeons have used HRQOL for research on parathyroidectomy (1999) 10 , colectomy (2002) 11 , laparoscopic hernia repair (2006) 12 , open inguinal hernia repair (2010) 13 Quality Improvement Program (ACSNSQIP) hospitals using the SF-36 instrument and found loss of independence associated with postoperative readmissions and death after discharge 15 . 20 .…”
mentioning
confidence: 99%
“…In Surgeons have used HRQOL for research on parathyroidectomy (1999) 10 , colectomy (2002) 11 , laparoscopic hernia repair (2006) 12 , open inguinal hernia repair (2010) 13 Quality Improvement Program (ACSNSQIP) hospitals using the SF-36 instrument and found loss of independence associated with postoperative readmissions and death after discharge 15 . 20 .…”
mentioning
confidence: 99%
“…Using new geriatric-specific variables from the American College of Surgeons National Quality Improvement Program Geriatric Surgery Pilot Project, the authors found that loss of independence occurred in 59.6% of surgical patients older than 65 years; 26.6% of patients demonstrated a decline in functional status, 32.0% demonstrated a decline in mobility, and 46.0% required increased care. 2 In regression analysis, loss of independence was associated with readmission (odds ratio, 1.7; 95% CI, 1.4-2.2) and death after discharge (odds ratio, 6.7; 95% CI, 2.4-19.3).…”
mentioning
confidence: 96%
“…In this issue of JAMA Surgery , Berian et al 2 examine the association between loss of independence (defined as a decline in functional status, deterioration in mobility, or new requirements for special services, such as new home care or skilled nursing facility needs) and 2 postoperative outcomes, readmission and death after discharge. Using new geriatric-specific variables from the American College of Surgeons National Quality Improvement Program Geriatric Surgery Pilot Project, the authors found that loss of independence occurred in 59.6% of surgical patients older than 65 years; 26.6% of patients demonstrated a decline in functional status, 32.0% demonstrated a decline in mobility, and 46.0% required increased care.…”
mentioning
confidence: 99%
See 2 more Smart Citations